Exploring Factors Affecting Buying Interest of Smartphones During the Covid 19 pandemic - PURWANTO, AGUS; Sudargini, Yuli (Journal of Industrial Engineering & Management Research, 2021)
This study aims to determine the effect of Brand Image and Sales Promotion on Interest in Buying Smartphones during the covid 19 pandemic. The research method used is a quantitative method with the type of survey method. The research technique used is probability with a snowball sampling approach, the respondents are 95 smartphone consumers. Data collection techniques using questionnaires distributed online. This research data processing using SmartPLS 3.0 software. The results of this study found that brand image and sales promotion affect interest in buying cellphones during the covid 19 pandemic.